Case report: A homozygous ADAMTSL2 missense variant causes geleophysic dysplasia with high similarity to Weill-Marchesani syndrome - Li, Mojiang; Li, Yingshu; Liu, Huixing; Zhou, Haiyan; Xie, Wanqin; Peng, Qinghua (Frontiers in Genetics, 2022)
Background Geleophysic dysplasia and Weill-Marchesani syndrome from the acromelic dysplasias group of genetic skeletal disorders share remarkable clinical and genetic overlap. Methods Ophthalmological, physical, radiological examinations were conducted with a female patient in her early 30s. Whole exome sequencing followed by Sanger sequencing validation was performed to identify the genetic cause. Results The patient, born to consanguineous Chinese parents, presented with microspherophakia, lens subluxation, high myopia, short statue, small hands and feet, stiff joints, and thickened skin. A diagnosis of Weill-Marchesani syndrome was initially made for her. However, genetic testing reveals that the patient is homozygous for the c.1966G>A (p.Gly656Ser) variant in ADAMTSL2, and that the patient’s healthy mother and daughter are heterozygous for the variant. As mutations in ADAMTSL2 are known to cause autosomal recessive geleophysic dysplasia, the patient is re-diagnosed with geleophysic dysplasia in terms of her genotype and phenotype. Conclusion The present study describes the clinical phenotype of the homozygous ADAMTSL2 p.Gly656Ser variant, which increases our understanding of the genotype-phenotype correlation in acromelic dysplasias.